(untitled) (Multidisciplinary Journal of Science and Technology, 2023)
The article presents the results of a study on the use of magnetite sorbents based on iron oxides (hematite). The sorption abilities of the resulting sorbents have been studied and the effectiveness of these sorbents for treating wastewater from natural cesium and strontium radionuclides has been proven.